Competitiveness of Indonesian beef trading in Asean - Sutawi, S.; Hendraningsih, L.; Wahyudi, A. (Diponegoro University, 2019)
This research was aimed to analyze Indonesian beef trading competitive position and specialization in ASEAN countries. This research was conducted in Indonesia with nine other ASEAN members (Brunei, Cambodia, Laos PDR, Malaysia, Myanmar, Philippines, Singapore, Thailand, and Vietnam) as the comparison. The research used secondary data of beef export and import values, and export commodities from Indonesia and nine other ASEAN countries in 2013 to 2017. Beef competitive position was measured by using Revealed Comparative Advantage (RCA) method, while the development of beef commodity in international trading was measured by using Trading Specialization Index (TSI) method. RCA calculation result in 2013-2017 showed the lowest comparative advantage of Indonesian beef trading in ASEAN (RCA = 0.000). TSI calculation result in 2013-2017 showed that Indonesian beef trading commodity was in introduction stage in international trading (TSI=-1.000).